LOW HBA1C; IS IT DAPSONE? - Khan, Haris; Nawaz, Maimoona (Journal of Ayub Medical College Abbottabad, 2018)
A 51-year-old male was referred to the diabetes clinic by the GP with low HbA1c (13 mmol/mol). His complaints were dizziness and intermittent palpitations for the last two years. No precipitating cause could be identified. He denied any chest pain, shortness of breath or syncope. He had a background of schizophrenia, epilepsy, coeliac disease, depression and dermatitis herpetiformis. He was on dapsone, venlafaxine, procyclidine, furosemide, diazepam, omeprazole, meloxicam and folic acid. On examination, his pulse was 82 beats per minute, blood pressure 131/74 mm of Hg, respiratory rate was 14/minute and his saturations on room air were 94%. Neurologic, cardiovascular, respiratory and abdominal examination was unremarkable. His investigations showed Hb of 121g/L (130-180) WCC 7.8*10¹g/L (4-11), platelets 182*10¹ (150-400), MCV 83 fl (80-100), TSH 2.53 mU/L (0.4-4.0 mU/L), anti TTG 14.9 (normal). Renal, liver function, serum folate, vitamin B12 and complement levels were within normal limits with a negative ANCA and ANA. His oral glucose tolerance test was negative for diabetes with fasting and two-hour post prandial blood sugar of 4.8mmol/L and 6.9 mmol/L respectively. Because of the history of chronic Dapsone use and possibility of drug induced low HbA1C, patient was investigated along those lines. The low Hba1c was attributed to haemolysis secondary to dapsone. HbA1c improved to 42 mmol/mol within three months following discontinuation of dapsone. His haemoglobin level also normalized (142g/L). Clinicians should consider haemolysis as a possible factor falsely reducing HbA1c while interpreting results in these patients. This is of particular importance in patients with diabetes. Keywords: Dapsone; HbA1c